Description of Knowledge Level of Nurses about Care of Covid-19 Patients in Tuan Rondahaim Hospital, Pamatang Raya Simalungun Regency - Maswan Daulay (Science Midwifery, 2022)
This study aims to describe the level of knowledge of nurses about covid-19 patient care. This research method uses a descriptive design. The sample used in this study were 38 nurses. The sampling technique was carried out using total sampling, which involved the entire population. The results showed that 31 (81.6%) people had good knowledge about covid-19 patient care, 6 (15.8%) people had sufficient knowledge and 1 (2.6%) people had less knowledge about treatment. covid-19 patients. Nurses have good knowledge about covid-19. However, the hospital still has to provide further information to medical staff for better control of infectious diseases.